1991
DOI: 10.1542/peds.88.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Dog Bites in Urban Children

Abstract: As a result of a perceived increase in pit bull injuries, all children who presented to The Children's Hospital of Philadelphia during 1989 for evaluation of dog bite injuries were prospectively studied. Epidemiologic information was collected from parents, either at the time of visit or by phone on the following day. A total of 168 children were enrolled; the mean age was 8 years. Males outnumbered females 1.5:1. Most (61%) injuries occurred in or around the home and involved dogs known to the patient (77%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Of the 43 included studies, 29 were retrospective chart reviews characterizing the epidemiology of dog bites and their associated treatment outcomes, with 1 using the National Trauma Database 2–6 8 9 15–36. Six studies were prospective cohort studies,7 37–41 two were cross-sectional studies,42 43 and six were experimental studies (five focused on educational/prevention interventions for children and adults and one focused on prophylactic antibiotic therapy) (online supplemental table 1). 10 44–48 Only 9 of the 43 studies had a behavioral health component incorporated into the study design or discussion sections 7 16 19 38 42–46…”
Section: Resultsmentioning
confidence: 99%
“…Of the 43 included studies, 29 were retrospective chart reviews characterizing the epidemiology of dog bites and their associated treatment outcomes, with 1 using the National Trauma Database 2–6 8 9 15–36. Six studies were prospective cohort studies,7 37–41 two were cross-sectional studies,42 43 and six were experimental studies (five focused on educational/prevention interventions for children and adults and one focused on prophylactic antibiotic therapy) (online supplemental table 1). 10 44–48 Only 9 of the 43 studies had a behavioral health component incorporated into the study design or discussion sections 7 16 19 38 42–46…”
Section: Resultsmentioning
confidence: 99%
“…The time span assessed in the studies ranged from 1985 to 2017 [4,9,11,. Majority of the included studies in the review were retrospective studies except 4 studies (2 were prospective studies [11,25] and 2 were cross-sectional questionnaire-based surveys [38,43]). The animals involved in the biting episode were dogs in all the included studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…For example, a disproportionate vulnerability exists for younger boys, those familiar with the attacking canine, and those with an increasing number of dogs in their household. [4][5][6][7][8] Specific dog breeds have been implicated with higher risk, particularly Pitbulls and other mixed breeds. 9,10 Recently it has been suggested that societal shutdowns in the wake of the coronavirus disease 2019 (COVID-19) pandemic have inadvertently precipitated a rise in incidence of dog-bites among pediatric ED visits.…”
mentioning
confidence: 99%